The potential for measles transmission in England - Fraser Graham; Gay Nigel; Choi Yoon; Ramsay Mary (BMC, 2008)
Abstract Background Since the schools vaccination campaign in 1994, measles has been eliminated from England. Maintaining elimination requires low susceptibility levels to keep the effective reproduction number R below 1. Since 1995, however, MMR coverage in two year old children has decreased by more than 10%. Methods Quarterly MMR coverage data for children aged two and five years resident in each district health authority in England were used to estimate susceptibility to measles by age. The effective reproduction numbers for each district and strategic health authority were calculated and possible outbreak sizes estimated. Results In 2004/05, about 1.9 million school children and 300,000 pre-school children were recorded as incompletely vaccinated against measles in England, including more than 800,000 children completely unvaccinated. Based on this, approximately 1.3 million children aged 2-17 years were susceptible to measles. In 14 of the 99 districts, the level of susceptibility is sufficiently high for R to exceed 1, indicating the potential for sustained measles transmission. Eleven of these districts are in London. Our model suggests that the potential exists for an outbreak of up to 100,000 cases. These results are sensitive to the accuracy of reported vaccination coverage data. Conclusion Our analysis identified several districts with the potential for sustaining measles transmission. Many London areas remain at high risk even allowing for considerable under-reporting of coverage. Primary care trusts should ensure that accurate systems are in place to identify unimmunised children and to offer catch-up immunisation for those not up to date for MMR.